Analisis Hubungan Sudut Hamburan terhadap Pergeseran Panjang Gelombang pada Efek Compton Menggunakan Simulasi GeoGebra - Lourensia Bravini Lahera; Agnes Viola Manik; Novita Zuraida; Nazhira Mizilfa; Samuel Baringbing; Michelle Belinda; Ade Ayu Lestari; Indah Vanesa Br. Ginting; Putri Najwa Nasution; Fitria Fadila Harisi; Septya Wulandari; Novia Novia (Kappa Journal, 2025)
The Compton effect is an important phenomenon in modern physics that demonstrates the quantum nature of light through the wavelength shift due to the scattering of photons by electrons. However, this concept is often difficult for students to understand because it is abstract and involves complex mathematical equations. This study aims to analyze the relationship between the photon scattering angle and the wavelength shift (Δλ) in the Compton effect using GeoGebra simulation as an interactive visualization medium. This study uses a qualitative descriptive method with GeoGebra as the main simulation instrument. Simulations are carried out based on the Compton equation by varying the photon scattering angle by 30°, 60°, and 120°, while the initial photon energy is set at 2.81 MeV. Data in the form of initial wavelength, scattered wavelength, and wavelength shift are analyzed qualitatively to interpret the physical relationship between variables. The simulation results show that the wavelength shift increases with increasing photon scattering angle, in accordance with the predictions of the Compton effect theory and the law of conservation of energy and momentum. In addition to strengthening conceptual understanding of the Compton effect, this study shows that GeoGebra is effective as a visual learning medium to help students understand quantum phenomena in a more concrete and communicative way.